Toward a model of relationship between the overall and the destination attributes satisfaction : an exploratory study - Najev Čačija, Ljiljana (Array, 2020)
This study presents a preliminary research towards a conceptual model of relationship between the overall and the destination attributes satisfaction. Precisely, the paper explores and classifies destination pull factors as a precondition to design a conceptual model. Therefore, the first step was to categorise destination attributes into meaningful groups of pull factors that provide greater efficiency in achieving and maintaining a desired perception of destination quality, measured by tourists’ satisfaction. The exploratory factor analysis was conducted on the sample of 289 tourists visiting the town of Split (Croatia). The required prior statistical preconditions were successfully met and the principal component analysis was conducted on 20 items with Varimax rotation method. Based on the results, four pull factors were retained in the final analysis, explaining 54.760% of the variance. In the final categorisation, factor loading was above 0.4 for all four extracted factors, with reliability of measurement scales. Major findings of this study confirm that destination attributes can be grouped in a meaningful way regarding tourist satisfaction and indicate that the extracted pull factors, representing both common and unique destination attributes, have the potential to be generally applicable. The extracted factors are the primary or fundamental offer components; additional/expanded offer components; tertiary or tendency/affinity/preference offer components and specific offer components. Recommendations for further research are given, in order to explore to what extent the tourists’ overall satisfaction is related to their satisfaction with destination attributes, and to expand the model with the impact of other moderating elements.